Racial Capitalism, Slavery, Labour Regimes and Exploitation in the Canadian Seasonal Agricultural Workers Program - Julie Ann McCausland (Caribbean Studies Students' Union, 2020)
This paper will attempt to critically examine Canada's Seasonal Agricultural Workers Program (SAWP) with an intent of connecting four themes: the Canadian agricultural industry, indentured servitude, the labour regime in Canada, and the racialization of the SAWP. It has been argued that the workers from the Caribbean who participate in the Temporary Agricultural Workers Program are should consider themselves fortunate to be given such an opportunity. I argue that this assertion is problematic because it overlooks the hardship the workers face in Canada as a result of their non-citizen status. I also examine the fact that many of the workers enlisted in the SAWP are forced to migrate for a living wage due to poor economic conditions in their countries of origin, and that these conditions are a direct consequence of unequal trade policies and structural adjustment programs. Finally, I demonstrate Canada's complicity in benefiting from these programs.